Quantum Theory A Wide Spectrum - Manoukian, E.B (Springer Netherlands : Imprint: Springer, 2006)
The ultimate modern textbook on Quantum Theory, this graduate-level and self-contained text is also a reference and research work which provides background for research in this discipline, covering important recent developments and most aspects of the theory with fairly detailed presentations. In addition to traditional topics, it includes: selective measurements, Wigner's Theorem of symmetry transformations, generators of quantum transformations, supersymmetry, details on the spectra of Hamiltonians and stability of quantum systems, Bose-Fermi oscillators, coherent states, hyperfine structure of the H-atom for any angular momentum, the non-relativistic Lamb shift, anomalous magnetic moment of the electron, Ramsey oscillatory fields methods, measurement, interference and the role of the environment, the AB effect, geometric phases (including the nonadiabatic and noncyclic), Schrödinger's cat and quantum decoherence, quantum teleportation and cryptography, quantum dynamics of the Stern-Gerlach effect, Green functions, path integrals, including constrained dynamics, quantum dynamical principle and variations, systematics of multi-electron atoms, stability of matter, collapse of "bosonic matter" and the role of spin, intricacies of scattering, quantum description of relativistic particles for any spin and mass, spinors, helicity, the Spin & Statistics Theorem. In addition it contains numerous problems, some of which are challenging enough for research. Audience: Instructors and graduate students in Physics, researchers and professional scientists in Theoretical Physics.